Biomarkers of response to ocrelizumab in relapsing–remitting multiple sclerosis - Fernando Rodríguez-Jorge; José Ignacio Fernández-Velasco; Noelia Villarrubia; Julia Gracia-Gil; Eva Fernández; Virginia Meca-Lallana; Carolina Díaz-Pérez; Susana Sainz de la Maza; Eva María Pacheco; Ana Quiroga; Lluis Ramió-Torrentà; Sergio Martínez-Yélamos; et al. (Frontiers in Immunology, 2024)
ObjectiveTo ascertain the changes of serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (sGFAP) values in relapsing–remitting multiple sclerosis (RRMS) patients treated with ocrelizumab and their association with treatment response.MethodsMulticenter prospective study including 115 RRMS patients initiating ocrelizumab treatment between February 2020 and March 2022 followed during a year. Serum samples were collected at baseline and every 3 months to measure sNfL and sGFAP levels using single-molecule array (SIMOA) technology. Based on age and body mass index, sNfL values were standardized using z-score. NEDA (non-evidence of disease activity)-3 status was defined for patients free of disease activity after a year of follow-up. Inflammation (INFL) was considered when new relapses occurred during follow-up or new MRI lesions were found at 1-year exploration. PIRA (progression independent of relapse activity) was defined as disability progression occurring in the absence of relapses or new MRI activity.ResultsAfter a year on ocrelizumab, 85 patients (73.9%) achieved NEDA-3. Thirty patients did not achieve NEDA: 20 (17.4%) because of INFL and 10 (8.7%) because of PIRA. Of INFL patients, 6 (30.0%) had relapses, and 17 (85.0%) had at least one new MRI lesion at the 12-month examination. At baseline, INFL patients had higher sNfL (p = 0.0003) and sGFAP (p = 0.03) than the NEDA-3 group. PIRA patients mostly exhibited low sNfL and heterogeneous sGFAP levels. After a year, NEDA-3 and INFL patients showed similar decreases in sNfL (p < 0.0001) and sGFAP (p < 0.0001 for NEDA-3 and p = 0.001 for INFL ones). However, the decrease occurred earlier in NEDA-3 patients. Accordingly, sNfL > 1.5 z-score 3 months after ocrelizumab initiation indicated a higher risk of inflammation (OR = 13.6; p < 0.0001). Decrease in sGFAP values occurred later in both groups, with significant reductions observed at 12 months for INFL and 6 and 12 months for NEDA-3. No significant changes in sNfL or sGFAP were observed in PIRA patients.ConclusionOcrelizumab induced normalization of sNfL and sGFAP in the majority of NEDA-3 and inflammatory patients but did not cause changes in the PIRA group. Our data suggest that normalization of sNfL and sGFAP is associated with the lack of inflammatory-associated disease progression but it may not affect non-inflammatory PIRA.